Primary Aldosteronism: Who Should be Screened? - Monticone, S.; Viola, A.; Tizzani, D.; Crudo, V.; Burrello, J.; Galmozzi, M.; Veglio, F.; Mulatero, P. (Hormone and Metabolic Research, 2012)
Primary aldosteronism (PA) has a prevalence in the general hypertensive population from 5 to 10%, and is widely recognized as the most frequent form of secondary hypertension. The 2 main PA subtypes are aldosterone producing adenoma (APA) and bilateral adrenal hyperplasia (BAH) that account for 95% of all PA cases. The diagnosis of PA is a 3-step process that comprises screening, confirmatory testing, and subtype differentiation. The different categories of patients at an increased risk of PA who should thus undergo a screening test were described in the first Endocrine Society (ES) Practice Guidelines for diagnosis and treatment of PA published in 2008. These categories include patients with Joint National Committee Stage 2, Stage 3, or drug-resistant hypertension; hypertension, and spontaneous or diuretic-induced hypokalemia; hypertension with adrenal incidentaloma; hypertension and a family history of early-onset hypertension or cerebrovascular accident at a young age and all hypertensive first degree relatives of patients with PA. Recently, a growing number of studies have linked PA with the metabolic syndrome, diabetes, and obstructive sleep apnea that may be partly responsible for the higher rate of cardio and cerobrovascular accidents in PA patients. The aim of this review is to discuss, which patients should be screened for PA, focusing not only on the well-established categories of the ES Guidelines, but also on additional other group of patients with a potentially high prevalence of PA that has emerged from recent research.
Keywords: primary aldosteronism; aldosterone; familial hyperaldosteronism; aldosterone-producing adenoma; endocrine hypertension